Stabilitasi Asimtotik Sistem Linear Pada Aljabar Bernorma = Asymtotic Stability of Linear Systems Over a Normed Algebra - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 1999)
ABSTRACT In this paper a block-input, block-output state model which was developed for the study of linear time-invariant discrete-time systems whose coefficients belong to an arbitrary commutative ring R with multiplicative identity 1 was discussed. This framework arose in the study of integer systems, whose coefficients depend on parameters and multi-dimensional systems. Based on the block-input form of linear systems, the problem of stabilization for linear systems whose coefficients belong to a commutative normed algebra was studied.